SAT0130 Rheumatoid Arthritis Related Interstitial Lung Disease – is There an Association between Disease Modifying anti Rheumatic Drugs and Survival?. (10th June 2014) - Brown, M.; Kelly, C.; Nisar, M.; Arthanari, S.; Woodhead, F.; PriceForbes, A.; Middleton, D.; Dempsey, O.; Dawson, J.; Sathi, N.; Ahmad, Y.; Koduri, G.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is associated with interstitial lung disease (ILD). This is linked with an increased risk of early death from respiratory failure. There is debate on the relative safety of different disease modifying anti rheumatic drugs (DMARDs) in RA-ILD. Objectives: We have examined the effect of a range of DMARDs on all cause and respiratory mortality in a large multi centre UK wide retrospective study to address this issue. Methods: The British Rheumatoid InterstitiaL Lung (BRILL) network comprises clinicians from seven centres across the UK. We collected data on DMARD use in patients with both RA and ILD (proven on HRCT) identified over a 25 year period from 1987 to 2012 using a standard proforma. We also analysed the age, duration of both RA and ILD, outcome and, where appropriate, cause of death. Equivalent data were obtained from a control group of RA patients without lung disease, matched for age, sex and disease duration. We recorded the number of patients with RA-ILD on each of six commonly prescribed DMARDs, including methotrexate. We used Chi squared tests to assess the significance of any differences in disease characteristics between patients on different DMARDs. We calculated relative risk (RR) for all cause and respiratory mortality in patients with RA-ILD treated with each of these agents. Results: A total of 260 patients were identified from across the UK with proven RA-ILD. DMARDs had been prescribed in 218 (84%) patients, and comprised methotrexate (52%), sulphasalazine (50%), leflunomide (21%), hydroxychloroquine (19%), gold salts (14%) and penicillamine (5%). Over half of patients had received at least two different DMARDs. There were no differences between the patients on different DMARDs with regard to age, gender, disease duration, subtype and extent, smoking, serology and lung function. The RR of death from any cause and from respiratory disease were not significantly increased by any commonly used DMARD. Specifically, methotrexate was not associated with any excess increase in mortality. However, gold salts were associated with a RR of 5.3 for death from respiratory disease, although numbers were small. Relative risk (RR) of death in RA patients on DMARDs Conclusions: Patients with RA-ILD have increased mortality compared to controls. Most are treated with DMARDs for their articular disease. There is no evidence to relate the more commonly used agents to the increase in mortality. This large retrospective BRILL network study suggests that it is safe to prescribe most DMARDs, including methotrexate, to patients with RA-ILD, although caution should be shown in the use of gold salts. Acknowledgements: Kieran Kelly for preparing the database Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1246